Pengaruh Varian Menu, Harga dan Suasana Café Terhadap Kepuasan Konsumen di Kedai Retro Coffe - Garil Adiyat Maulana; Muhajirin; Muliyadin (Teewan Journal Solutions, 2025)
To determine the influence of menu variants, prices and café atmosphere on consumer satisfaction at Kedai Retro Coffee. (The type of research used in this research is associative. This research aims to determine the effect of menu variants, prices and cafe atmosphere on consumer satisfaction at Kedai Retro Coffee. Based on the results of the analysis, it is known that F count is 13.556 > F table 3.09 and the sig value. 0.000 < 0.05 which means hypothesis H3 is accepted. It can be concluded that menu variants, prices and café atmosphere have a significant effect on consumer satisfaction at Kedai Retro Coffee.